Relationship Between Pregnant Women's Knowledge, Husband's Support and Pregnant Women's Attitude with Triple Elimination Screening Examination at Cakranegara Community Health Center - Subawa, Pande Putu Bagus Eka; Karmila, Dany; Sukmajaya, Ali; Sayang, I Nyoman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pregnant women must undergo routine check-ups in a check-up package called Antenatal Care (ANC). One of the ANC service packages that pregnant women must follow is the Triple Elimination screening examination which can prevent 3 infectious diseases, namely Human Immunodeficiency Virus (HIV), hepatitis B, and syphilis which can be transmitted from mother to fetus. The purpose of this study was to determine the relationship between knowledge of pregnant women, husband's support and attitudes of pregnant women with the Triple Elimination screening examination in the working area of ​​the Cakranegara Health Center. cross-sectional research using quantitative methods. Simple random sampling is the method used for sampling. The Cakranegara Community Health Center served as the site of the study. There were 110 responders in the research sample. The Chi-Square test was used to evaluate the data, and a significant result of p < 0.05 was found. Among the 110 pregnant women who responded, 58.2% had high knowledge (p-value = 0.011), 50.9% had positive husband support (p-value = 1.000), and 73.6% had positive attitudes (p-value = 0.001) among those who responded about pregnant women's attitudes. While there is a correlation between pregnant women's attitudes and their level of knowledge regarding the Triple Elimination screening examination at the Cakranegara Community Health Center, there is no significant correlation between husband support and the test.